Peran UMKM dalam perekonomian Indonesia: Peluang, tantangan, dan kebijakan untuk meningkatkan daya saing - Maulana, Much. Rizki; Baihaqi, Khalif (Maliki Interdisciplinary Journal, 2024)
The strategic role of micro, small and medium enterprises (MSMEs) in the Indonesian economy makes a positive contribution to job creation, regional development and economic integration. Even though they have great potential, MSMEs also face various challenges, including limited access to financing and infrastructure constraints. This research uses descriptive-analytical methods to examine the role of MSMEs in the Indonesian economy, with a focus on opportunities, challenges and policies to increase competitiveness. Data was obtained from primary sources including government and secondary sites including the latest research in the form of articles, journals, books and related scientific publications. This journal describes various efforts that can be made to increase the competitiveness of MSMEs by considering opportunities such as digital technology and improving skills. The focus is on strengthening public-private partnerships, financial innovation, digital ecosystem development, skills development, and policy oversight. Although there are potential obstacles such as policy continuity, bureaucracy, and access gaps, this journal believes that if these steps are implemented effectively, the role of MSMEs in supporting economic growth throughout Indonesia will increase.